Formation static output control of linear multi-agent systems with hidden Markov switching network topologies. - Rodriguez Canales, Eduardo Steve (2021)
This dissertation addresses the H2, H and mixed H2/H formation static output control of continuous-time linear multi-agent systems with Markovian switching network topologies. It is assumed that the mode of operation of the network topology cannot be directly measured but, instead, can be estimated by an imperfect detector. To model this problem we consider a continuous-time hidden Markov model, in which the hidden component represents the real mode of operation of the network topology while the ob served component represents the information emitted from the detector and available for the controller. It is also assumed that only a partial information from the state vari ables of the multi-agent systems is available. By using an LMI (linear matrix inequality) formulation, a distributed static output controller which switches according to the de tector information is designed to guarantee the stability in the mean square sense of the closed-loop system as well as an upper bound for an index performance. Three situations are considered for the performance criteria: the H2 norm, the H norm, and the mixed H2/H norms. This work is concluded with numerical examples to illustrate the effec tiveness of the theoretical results.